Mapping the Spread of Innovation in Multidisciplinary Applied Engineering Fields: A Review and Bibliometric Analysis - Mohamad Izzur Maula; M. Danny Pratama Lamura; Sakarinto, Wikan (Multidisciplinary Innovations and Research in Applied Engineering, 2025)
Applications of engineering have developed to numerous sectors and generated cross- and multidisciplinary studies to the academic world and global practitioners. The present study conducts a bibliometric examination and network visualization of applied engineering studies between 2014 and 2024, based on data taken from the Scopus database. Focus on studies included within the subject area multidiscipline, the examination delves into international linkage research, author-delineated themes, and index keyword arrangements to identify emerging tendencies and conceptual aggregations. Visualization conducted with the help of VOSviewer identifies the dominance of nations like China, the United States, and the United Kingdom both by publishing output as well as collaborative strength, with increasing participation by emerging nations like India, Saudi Arabia, and Iran. Author keyword examination identifies conventional sectors of engineering like mechanical, chemical, and electrical engineering, along with computational techniques like machine learning and optimization. On the other side, index keyword examination identifies the dominance of bioengineering themes involving metabolism, genetics, tissue engineering, and gene expression, with these terms possessing the greatest overall link strengths within the collection. By charting innovation across conceptual as well as geographic dimensions, the paper outlines the intricate, intertwined character of the contemporary applied engineering.